G-quadruplex motifs prediction and visualization in Sus scrofa genome - Šislerová, Lucie; Petrovič, Michal; Dobrovolná, Michaela; Šťastný, Jiří; Rozmaric, Tomaz; Dworak, Helene; Kratochvilová, Libuše; Veselá, Lenka; Schädl, Barbara; Gruber, Florian; Grillari, Johannes; Freystätter, Christian; et al. (My University, 2026)
Sus scrofa is not only a key agricultural species but also a valuable biomedical model due to its physiological and anatomical similarities to humans. We present a comprehensive genome-wide analysis of putative G-quadruplexforming sequences (PQS) in the pig genome, with a focus on their distribution within regulatory and functionally relevant genomic regions. Our results demonstrate that PQS are non-randomly distributed, showing significant enrichment in promoter regions, untranslated regions, and other regulatory elements. These distribution patterns closely parallel those observed in the human genome, suggesting a conserved role for G-quadruplexes (G4s) across species. Importantly, we provide experimental validation of G4 structures in cells in situ of porcine dorsal skin samples using the G4-specific antibody SG4, confirming their presence at the cellular level. The high degree of similarity in PQS localization between pigs and humans highlights the translational potential of Sus scrofa for studying G4 biology and evaluating G4-targeted therapeutic strategies.
Keywords: G-quadruplexes; Sus scrofa; Homo sapiens; Targeted therapies